Differential Expression of Aquaporin-3 and Aquaporin-5 in Pancreatic Ductal Adenocarcinoma - Direito, I (2021)
Submitted by Ana Quininha (ana.quininha@chlc.min-saude.pt) on 2021-08-13T14:12:54Z No. of bitstreams: 1 J Surg Oncol 2017 980.pdf: 19739170 bytes, checksum: b1556cbb50901f426dbf52ac67347925 (MD5)